Promoting investments in education in ASEAN: Inclusive education, cross-border education programs, and ICT capabilities - Fatharani Taqisa Nadhira (Center for Indonesian Policy Studies (CIPS), 2021)
This paper analyzes whether and how the ASEAN Work Plan on Education 2016-2020 promotes investment in education in the ASEAN Member States, focusing on three main areas: inclusive education, cross-border education programs, and ICT capacity building.
Keywords: 330; Bildungspolitik; Bildungsfinanzierung; Bildungschancen; ASEAN-Staaten